Muamalah dalam Islam: Memahami Konsep 'Ariyah dan Aplikasinya - Suarni Suarni (Sinthop, 2023)
The concept of 'Ariyah in Islam, within the framework of Muamalah (human interaction), holds a significant place in the social and economic aspects of Muslim life. This paper aims to explore the etymological and terminological dimensions of 'Ariyah and its practical implications in Islamic law. Employing a qualitative approach, this study draws on religious texts, including the Qur'an and Hadith, as well as scholarly works on Islamic jurisprudence. The analysis reveals that 'Ariyah, etymologically, is associated with the idea of borrowing and returning, and terminologically refers to the practice of utilizing another's possessions without compensation. This concept encompasses values of generosity and unconditional giving, with slight variations across Islamic schools of thought. The validity of 'Ariyah transactions in Islamic law depends on certain pillars and conditions, such as the declaration of borrowing, the ownership status of the lender and borrower, and the nature of the borrowed item. The concept of 'Ariyah aligns with the broader Islamic ethos of assistance and reciprocal cooperation, particularly in the practice of lending.